2003
DOI: 10.1016/s1525-0016(03)00098-4
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus serotype 4 mediates unique and exclusive long-term transduction of retinal pigmented epithelium in rat, dog, and nonhuman primate after subretinal delivery

Abstract: We previously described chimeric recombinant adeno-associated virus (rAAV) vectors 2/4 and 2/5 as the most efficient vectors in rat retina. We now characterize these two vectors carrying the CMV.gfp genome following subretinal injection in the Wistar rat, beagle dog, and cynomolgus macaque. Both serotypes displayed stable GFP expression for the duration of the experiment (6 months) in all three animal models. Similar to the AAV-2 serotype, AAV-2/5 transduced both RPE and photoreceptor cells, with higher level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 45 publications
(35 reference statements)
1
113
1
3
Order By: Relevance
“…25 Additional studies with these two vectors have confirmed that AAV-2/5 transduces both RPE and photoreceptor cells in rat and dog, with photoreceptors being more efficiently transduced than with AAV-2/2. 26 More importantly, this study demonstrated that the type 4 capsid allows exclusive and stable transduction of RPE cells, and that this feature is conserved among rodent, canine and non-human primate models. Similar to the chimeric rAAV-2/5 vector, subretinal injection of a complete rAAV-5/5 vector in mouse shows faster expression kinetics and results in higher transduction efficiency compared with rAAV-2/ 2, 27 with RPE cells and photoreceptors being transduced in both case.…”
Section: Raav Serotypes and Tropismmentioning
confidence: 64%
See 2 more Smart Citations
“…25 Additional studies with these two vectors have confirmed that AAV-2/5 transduces both RPE and photoreceptor cells in rat and dog, with photoreceptors being more efficiently transduced than with AAV-2/2. 26 More importantly, this study demonstrated that the type 4 capsid allows exclusive and stable transduction of RPE cells, and that this feature is conserved among rodent, canine and non-human primate models. Similar to the chimeric rAAV-2/5 vector, subretinal injection of a complete rAAV-5/5 vector in mouse shows faster expression kinetics and results in higher transduction efficiency compared with rAAV-2/ 2, 27 with RPE cells and photoreceptors being transduced in both case.…”
Section: Raav Serotypes and Tropismmentioning
confidence: 64%
“…29 For chimeric vectors rAAV-2/5 and rAAV-2/4, subretinal injection in dogs results in stable expression of GFP for more than 18 months (Rolling et al, data not shown), with the tropism being identical to the one observed in the rat: transduction of RPE and photoreceptor cells with type 5 and exclusive transduction of RPE with type 4. 26 …”
Section: Gene Transfer In Large Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…rAAV-2/4 allowed exclusive and stable transduction of RPE cells in rodent, canine and non-human primate models. 9 Stable gene transfer into the retina using lentiviral vectors was also reported. Early studies demonstrated conflicting results when determining the tropism of HIV vectors pseudotyped with vesicular stomatitis virus G glycoprotein (VSV-G).…”
mentioning
confidence: 99%
“…In a rAAV or lentiviral context, both of these promoters allowed stable expression of the transgene. 9,13 The RPE-specific promoter versus the ubiquitous CMV promoter does not prevent the progressive loss of detectable GFP signal in HSV-1 amplicon-transduced retinas. In contrast to lentiviral vectors, which integrate into the chromosome, the HSV-1 amplicon remains episomal.…”
mentioning
confidence: 99%